Novel Bovine Plasma Protein Film Reinforced with Nanofibrillated Cellulose Fiber as Edible Food Packaging Material - Shihan Weng; Sara Sáez-Orviz; Ismael Marcet; Manuel Rendueles; Mario Díaz (Membranes, 2021)
Proteins, such as those in blood from slaughterhouses, are a good option for developing edible films. However, films made exclusively from proteins have low strength and high water solubility, which makes them difficult to use in the food industry. The use of cellulosic material, such as nanofibrillated cellulose (NFC), can improve the properties of these films. In the present work, bovine plasma was acidified and treated with ethanol to precipitate its proteins, and these proteins were used to prepare films reinforced with several concentrations of NFC. In addition, control films prepared with untreated bovine plasma and reinforced with NFC were prepared as well. These new edible films were characterized according to their mechanical properties, water vapor permeability, light transmittance, and microstructure. Furthermore, the film with the best properties was selected to be additivated with nisin to test its antimicrobial properties by wrapping meat previously contaminated with Staphylococcus aureus. In this sense, films prepared with the extracted proteins showed better properties than the films prepared with untreated plasma. In addition, the results showed that the reinforcement of the films with a 10% (w/w) of NFC decreased their water solubility and improved their puncture strength and water vapor barrier properties. Finally, the addition of nisin to the films prepared with extracted protein from bovine plasma and NFC gave them antimicrobial properties against S. aureus.